Hittite landscape and geography - Weeden, Mark; Ullmann, Lee Z.; Homan, Zenobia (Handbook of Oriental studies, 2017)
Perspectives based Primarily on Archaeological Evidence -- The Land of the Hittites : Airs, Waters and Places / Neil Roberts -- The Discovery of a Hittite City Developments in Hittite Geography based on the Identification of Ortakoy-Sapinuwa / Aygul Suel and Mustafa Suel -- Hattusa and its Environs : Archaeology / Andreas Schachner -- Central East : Archaeology. Alacahoyuk, Eskiyapar, Ortakoy, Masathoyuk / Tunc Sipahi, Aygul Suel, Mustafa Suel, and Mark Weeden -- The East : Archaeology. The Upper Land, Azzi-Hayasa, Isuwa / Andreas Muller-Karpe -- The North : Archaeology / Claudia Glatz -- South-Central : Archaeology / Alvise Matessi and Bianca Maria Tomassini Pieri -- Central West : Archaeology / Kimiyoshi Matsumura and Mark Weeden -- The West : Archaeology / Sevinc Gunel -- Kizzuwatna : Archaeology / Mirko Novak and Susanne Rutishauser -- The Euphrates States and Elbistan : Archaeology / Michael Brown and Tony J. Wilkinson -- The Northern Levant : Archaeology / Jesse Casana